PERANAN PENGAWAS DALAM PENINGKATAN KUALITAS GURU MADRASAH IBTIDAIYAH DI KOTA SIBOLGA - Zulkifli Tanjung, dkk. (STIT Al-Ittihadiyah Labuhanbatu Utara, 2021)
This study aims to determine the role of supervisors in improving the quality of madrasah ibtidaiyah teachers; identify the constraints faced by the supervisor in carrying out supervision; and identify the techniques used by supervisors in carrying out supervision. To meet these objectives, researchers conducted descriptive qualitative research through data collection with interviews, observations and documented data. The data that has been obtained is then analyzed with a mixture of relevant references through stages, data reduction, data presentation and data verification. From the results of the research, it is known, namely: (1) that the supervisor has played a role in carrying out the supervisory duties through the stages of preparing the supervision program planning and making a visit schedule involving the head of the madrasah and the teachers, making a list of teacher stuffing and supervision instruments, (2) Teacher supervision is carried out individually with a humanist approach in carrying out supervision, (3) some of the constraints encountered by supervisors include the unanisance of IT facilities and audio visual devices, especially in private madrasahs for the development of ICT-based learning models and still low teacher commitment to the responsibility of presenting quality learning to learners. The supervision program is declared effective if it is able to supervise all madrasahs and target teachers who are the responsibility of the supervisor. Given the considerable ratio of the number of supervisors and teachers, the superintendent of madrasah ibtidaiyah Sibolga city prepared it by optimizing the madrasah KKG container through regular meetings of madrasah teachers once a month.